Spontaneous groin enterocutaneous fistula following neglected inguinal hernia in 3-month infant spontaneous enterocutaneous fistula following neglected inguinal hernia leading to groin enterocutaneous fistula in 3-month infant - Lawal Barau Abdullahi; Mamuda Atiku (Wolters Kluwer Medknow Publications, 2022)
Hernia is defined as a protrusion of part or whole of a viscera through an abnormal opening in the wall of the cavity containing the viscera. Strangulation of the viscera within the hernial sac is a common complication in our environment, and this occurs in both adult and children. We study the presentation and management of a 3-month-old infant with groin enterocutaneous fistula following a neglected inguinal hernia. A 3-month-old infant presented late with perforated intestine in an inguinal hernia and managed by the resection and anastomosis of the small intestine. The outcome of a neglected inguinal hernia is still poor in our environment.